Faktor Hygiene dan Motivator sebagai Variabel Moderating dalam Hubungan antara Partisipasi Penyusunan Anggaran dan Kinerja Manajerial - Huda, Arifatul; Nurkholis, Nurkholis (TEMA, 2004)
This study examines the role of job satisfaction consisting of hygiene factor and motivator as moderating variables in the relation between budgetary participation and managerial performance. Data were collected by sending questionnaires to manufacturing companies in Malang. Based on the result of regression analysis, this study found that participation has positive and significant effect on managerial performance. However, hygiene factor (extrinsic motivation) and motivator (intrinsic motivation) did not moderate the effect of participation in budgeting process on managerial performance.Keywords: participation, budgeting, job satisfaction, hygiene factor, motivator factor.